Multiplicação de Diaphorina citri e de Candidatus Liberibacter asiaticus em híbridos de citros indicados como porta-enxerto - Baia, Ana Dulce Botelho [UNESP] (2015)
Huanglongbing (HLB), or greening, is a disease that in Brazil is associated to the Candidatus Liberibacter asiaticus and Ca. Liberibacter americanus, both transmitted by the insect Diaphorina citri Kuwayama (Hemiptera: Liviidae). HLB is a disease highly destructive and of difficult control. Nowadays Ca. L. asiaticus ismost frequently found in citrus orchards. No commercial variety is resistant to the pathogen or insect vector. In order to satisfy grower necessity for more productive rootstocks and that promote smaller canopies to facilitate harvesting, several new hybrids have been tested for planting in the last years, For these hibrids no information exist on their potential in limiting the multiplication of the HLB bacteria or the vector, which could be used in disease management. In view of this, the objective of the present work was to evaluate multiplication rates of Ca. L. asiaticus and D. citri on five new hybrids suitable for use as rootstocks. For comparison purposes, the commercial rootstocks 'Cravo' Rangpur lime, 'Swingle' citrumelo, Poncirus trifoliata, and 'Sunki' mandarin, the sweet orange variety 'Valencia', and the ornamental orange jasmine Murraya exotica also were included in the study. D. citri multiplication was determined in healthy young shoots by daily counting of the number of eggs, nymphs and adults generated from two adult mating pairs, after confining them for 72 hours on the shoots or until eggs were observed. Ca. L. asiaticus multiplication was evaluated by quantitative PCR on the aerial part and roots of the plants, six months after stem graft inoculation. Influence of genotypes was observed on the multiplication of the insect as well as on the multiplication of the bacteria. The higher number of eggs was found on the hybrid 81G513 and on the orange 'Valencia', and the lower number of eggs on P. trifoliata. Nymph viability was higher on orange jasmine and P. trifoliata and lower on the ...